Prevalence and Associated Risk Factors of Glaucoma in Aligarh, India – A population based study - Anees Ahmad; Syed Zulfequar Ahmad; Najam Khalique; Mohammad Ashraf; Yasir Alvi (Delhi Journal of Ophthalmology)
Background: Glaucoma is one of the most common causes of blindness. Being irreversible, its early detection and management are utmost important. With increasing life expectancy, the prevalence of glaucoma is expected to rise. We did this study to find the prevalence of glaucoma among middle-aged and elderly population and to find out its associated factors. Methods: A community based cross-sectional study among rural and peri-urban area of Aligarh was done for a duration of one year. A trained ophthalmologist interviewed and examined 680 patients with a detailed eye examination. Intraocular pressure (IOP) was measured by Keeler pulsair non-contact tonometer, confirm by applanation tonometry. Anderson criteria were used to diagnose glaucomatous visual field defect. Results: In our study population, a total of 31 subjects were diagnosed as glaucoma in either one or both eyes. The overall prevalence of glaucoma was found to be 4.6%. About equal distribution of type of glaucoma, i.e. Primary Open Angle Glaucoma (POAG), Primary Angle Closure Glaucoma (PACG) and Normotensive Glaucoma (NTG) was observed in our study participants. The prevalence of glaucoma was found to be significantly associated with increasing age, positive family history as well as a history of angle closure. Conclusion: The prevalence of glaucoma is higher in the population of Aligarh. Its association with increasing age, positive family history and history of angle-closure may give us clues for early detection. Screening for glaucoma during middle age especially among person with a positive family history or angle-closure would help us early diagnosing and management of this irreversible disease.